SPECTRUM OF BRAIN ABNORMALITIES DETECTED ON WHOLE BODY F-18 FDG PET/CT SCAN - Hassan, Aamna; Majeed, Yasir; Aftab, Khurram (Journal of Ayub Medical College Abbottabad, 2017)
Positron emission tomography (PET) with integrated computed tomography (CT) is a unique modality to noninvasively scan the whole body for diagnosing, staging and assessing response to therapy in various benign and malignant diseases. 18F fluorodeoxyglucose (FDG) is the most commonly used radiotracer for PET/CT imaging in cancer patients. FDG is a glucose analogue which is the predominant substrate for brain metabolism. As the brain cells are obligate glucose consumers, the knowledge of physiologic radiotracer uptake within the brain is imperative for correct interpretation of abnormal sites of metabolism. Over 10,000 PET/CT scans have been performed at our centre in a 5 years’ period. A spectrum of brain abnormalities, both benign and malignant, detected in cancer patients undergoing whole body 18F FDG PET/CT imaging has been compiled. Keywords: Fluorodeoxyglucose; Positron Emission Tomography; Computed Tomography; Magnetic Resonance Imaging; Brain Tumours, Brain Metastasis; Benign Cerebral Lesions